2021
DOI: 10.3390/polym13081228
|View full text |Cite
|
Sign up to set email alerts
|

pH/Thermo-Responsive Grafted Alginate-Based SiO2 Hybrid Nanocarrier/Hydrogel Drug Delivery Systems

Abstract: We report the preparation of mesoporous silica nanoparticles covered by layer by layer (LbL) oppositely charged weak polyelectrolytes, comprising poly(allylamine hydrochloride) (PAH) and a sodium alginate, highly grafted by N-isopropylacrylamide/N-tert-butylacrylamide random copolymers, NaALG-g-P(NIPAM90-co-NtBAM10) (NaALG-g). Thanks to the pH dependence of the degree of ionization of the polyelectrolytes and the LCST-type thermosensitivity of the grafting chains of the NaALG-g, the as-prepared hybrid nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…We attribute these differences in SiNP mediated effects on drug release rates (and mechanical properties) to differences in the extent to which the nanoparticles may interact with the polymer chains. While it has been reported that alginate may non-covalently associate with silica nanoparticle surface [41], there are no published works (to the best of our knowledge) demonstrating positive interactions between agarose and silica nanoparticles.…”
Section: Drug Release Rates In Double-network Hydrogelsmentioning
confidence: 83%
See 1 more Smart Citation
“…We attribute these differences in SiNP mediated effects on drug release rates (and mechanical properties) to differences in the extent to which the nanoparticles may interact with the polymer chains. While it has been reported that alginate may non-covalently associate with silica nanoparticle surface [41], there are no published works (to the best of our knowledge) demonstrating positive interactions between agarose and silica nanoparticles.…”
Section: Drug Release Rates In Double-network Hydrogelsmentioning
confidence: 83%
“…We attribute these differences in SiNP mediated effects on drug release rates (and mechanical properties) to differences in the extent to which the nanoparticles may interact with the polymer chains. While it has been reported that alginate may noncovalently associate with silica nanoparticle surface [41], there are no published works (to the best of knowledge) demonstrating positive interactions between agarose and silica nanoparticles. Finally, we performed experiments to confirm that the differences in drug release rates were biologically relevant, i.e., differences in drug release rates from the different hydrogel formulations translate to differences in compound-mediated cell viability.…”
Section: Drug Release Rates In Double-network Hydrogelsmentioning
confidence: 99%
“…The coating with alginate is generally achieved by electrostatic interactions between the anionic biopolymers and the MSNs surface, made positive by appropriate functionalization [ 205 ]. Moreover, alginate is used in combination with positive polymers to create composite coatings by the already mentioned LbL self-assembly technique [ 206 , 207 , 208 ]. For instance, two recent studies used alginate in combination with chitosan for the formulation of pH-responsive polyelectrolyte-coated MSNs in the treatment of cancer [ 144 ] and neurodegenerative diseases [ 187 ].…”
Section: Functionalization Of Msns With Biopolymersmentioning
confidence: 99%
“…329,330 Some polyelectrolyte multilayers have pH-dependent ionization degree, near-infrared light, and thermal sensitivity, and the resulting polymers show good pH, light, and thermal responsiveness, which provides a basis for targeted drug release. 331–333…”
Section: Applicationsmentioning
confidence: 99%
“…329,330 Some polyelectrolyte multilayers have pH-dependent ionization degree, near-infrared light, and thermal sensitivity, and the resulting polymers show good pH, light, and thermal responsiveness, which provides a basis for targeted drug release. [331][332][333] 4.2.2 Hydrogels. As mentioned above, self-assembled hydrogels have reliable biocompatibility compared with the hydrogels formed by chemical cross-linking and possess the general properties inherent in hydrogels, including high water content and network-like structure.…”
Section: Drug Deliverymentioning
confidence: 99%